The digitalisation of industry from a strategic perspective - Oks, Sascha Julian; Fritzsche, Albrecht; Lehmann, Claudia (R&D Management Conference (RADMA), 2016)
Being exposed to technical change with potentially disruptive consequences for their own business operations, managers often hesitate to adopt it. This is currently the case for the digitalisation of industry. We argue in our paper that this is the result of a lack of strategic reflection: in order to engage more actively with innovations of this kind, managers need to put new technical devices in a business context where they can assess them with respect to certain purposes and success criteria. An empirical study on the introduction of a cyber-physical system for industrial maintenance in a variety of different fields of industry provides detailed information about how this is done. Problem-centred interviews are used to collect data on the various ways how decision makers in industry connect innovations in the course of digitalisation to strategic thought. The results highlight important differences between the respective application domains and the stakeholders who are affected by the innovatio
Keywords: digitalisation; industry 4.0; cyber-physical systems